FEATURES OF THE DOMESTIC INVESTMENT ENVIRONMENT - Levchenko, Oleksandr (Current Problems of Sustainable Development, 2026)
The article examines the features of Ukraine’s contemporary investment environment under martial law and the transformational processes associated with post-war economic recovery and European integration. The essence of the investment environment is defined as a set of economic, institutional, regulatory, financial, and socio-political factors that determine the conditions for investment activities and the level of a country’s investment attractiveness. The key characteristics of the domestic investment environment are identified, including elevated security risks, regional asymmetry of investment activity, institutional transformation, limited access to financial resources, and the increasing role of international financial support. A comparative analysis of the parameters of Ukraine’s investment environment before and after the onset of the full-scale invasion by the russian federation was conducted. The study found that military actions have significantly altered the regional structure of investment flows, sectoral priorities, and mechanisms of state support for investors. The dynamics of foreign direct investment were examined, revealing the unstable nature of investment recovery amid persistently high levels of risk. Increased investor interest was identified in sectors related to food security, energy, logistics, the defense industry, and agricultural processing. The study substantiates that enhancing Ukraine’s investment attractiveness requires the implementation of a comprehensive state policy aimed at ensuring macroeconomic stability, improving the institutional environment, developing mechanisms for war-risk insurance, protecting investors’ rights, and strengthening international investment cooperation. It is established that Ukraine’s current investment environment is undergoing a transformation process, combining significant risks with new opportunities emerging from reconstruction efforts, digitalization, and European integration.